High-performance artificial nitrogen fixation at ambient conditions using a metal-free electrocatalyst - Weibin Qiu (Nature Portfolio, 2018)
Electrochemical reduction of nitrogen is a promising route to industrial-scale nitrogen fixation at ambient conditions, but is challenged by activation of inert nitrogen. Here the authors report a metal-free catalyst that selectively reduces nitrogen to ammonia with high efficiency and stability.